(untitled) (University of Thi-Qar Journal for Engineering Sciences, 2014)
Dynamic analysis of coaxial dual rotor system was demonstrated in this paper through the use of finite element script files developed using matlab. A coaxial rotor system, generally employed in the aircraft engines to save space and keep the weight to minimum, and for the importance of this application it was considered for this analysis. The system was modeled using eight finite elements only with different shafts and bearings properties. The results obtained in this investigation were closed to other previous studies found in the literature. The developed matlab script files proved to be very essential for designers and analyst of coaxial rotors.